Study on the Influences of Empty Hole and In Situ Stress on Blasting-Induced Rock Damage. (8th May 2021) - Meng, Ningkang; Bai, Jian-biao; Shen, Wenlong; Chen, Yong; Wang, Xiangyu; Wu, Wenda; Wu, Bowen
Abstract : Blasting has been used extensively in deep underground excavation. In this paper, a numerical simulation LS-DYNA was carried out to investigate the influence of in situ stress and empty hole on rock fracture development. Based on the simulation process and existing laboratory data, the micromechanical properties of the Riedel-Hiermaier-Thoma (RHT) model were calibrated. By then, this model was used to study the effects of in situ stress and empty hole on the degree of damage and fracture development in the rock. Simulation results revealed that the difference between horizontal and vertical principal stresses can influence the degree of damage as well as the fracture initiation and development, which in turn leads to the fracture development towards a high-stress concentration area. Numerical simulation also showed that the total area of fracture development gradually decreases with the increasing in situ stress magnitudes. Under the same stress conditions, empty hole can facilitate the fracture development at 90°, while preventing the subsequent fracture development at 60° and 120°. This would result in further fracture propagation at 90°, such that the control of fracture direction can be achievable.